A NEW LATE TRIASSIC VERTEBRATE ASSEMBLAGE FROM NORTHWESTERN ARGENTINA (Ameghiniana, 2015)
The Quebrada del Barro Formation (QBF) is part of the continental Marayes-El Carrizal Basin, in NW Argentina. Here we report a diverse faunal assemblage recently discovered in the Quebrada del Barro Formation, along with a preliminary discussion of the taxonomic status and affinities of numerous vertebrate specimens found at two localities where this unit is exposed. The new vertebrate association includes remains of at least 12 different new species related to six major vertebrate groups: Cynodontia, Testudinata, Sphenodontia, Pseudosuchia, Pterosauria, and Dinosauromorpha. The most abundant specimens in this faunal assemblage are opisthodontian sphenodonts, tritheledontid cynodonts and basal sauropodomorph dinosaurs, but the assemblage also includes diagnostic remains of lagerpetid dinosauromorphs, theropods, pterosaurs, basal crocodylomorphs, and stem testudinatans. Several of these groups have also been reported for the Los Colorados Formation (LCF), although the two units differ in their taxonomic content at the species level and in the relative abundance of different taxonomic groups. A comparison of these two faunal assemblage suggest the fauna of QBF is younger than that of LCF and we tentatively assess a late Norian–Rhaetian age for the QBF. Some of the specimens reported here are known from well-preserved specimens and yield important new information for understanding the evolution of these groups, which underscores the relevance of the QBF fauna for assessing the dynamics of the major groups of vertebrates that dominated the terrestrial ecosystems during the early Mesozoic in Pangea.Resumen. UNA NUEVA ASOCIACIÓN DE VERTEBRADOS DEL TRIÁSICO TARDÍO DEL NOROESTE DE ARGENTINA. La formación Quebrada del Barro (QBF) es parte de la Cuenca continental Marayes-El Carrizal, en el noroeste de Argentina. Acá reportamos una diversa asociación faunística recientemente descubierta en la Formación Quebrada del Barro, junto con una discusión preliminar del estado taxonómico y afinidades de los numerosos especímenes de vertebrados encontrados en dos localidades de esa unidad. La nueva asociación de vertebrados incluye restos de al menos 12 diferentes nuevas especies relacionadas a seis grupos mayores de vertebrados: Cynodontia, Testudinata, Sphenodontia, Pseudosuchia, Pterosauria, and Dinosauromorpha. Los especímenes más abundantes en esta asociación faunística son esfenodontes opisthodontes, cinodontes tritheledóntidos y dinosaurios sauropodomorfos basales, pero la asociación también incluye restos diagnósticos de dinosauromorfos lagerpétidos, terópodos, pterosaurios, crocodilomorfos basales y stem testudinates. Varios de estos grupos han sido reportados también para la Formación Los Colorados (LCF), aunque las dos unidades difieren en su contenido taxonómico a nivel específico y en la abundancia relativa de los diferentes grupos taxonómicos. La comparación de estas dos asociaciones faunísticas sugiere que la fauna de QBF es más joven que la de LCF y tentativamente asignamos una edad Noriano-Retiano para QBF. Algunos de los especímenes reportados acá son conocidos por especímenes bien preservados y cuentan con importante nueva información para el entendimiento de la evolución de esos grupos, que pone de manifiesto la relevancia de la fauna de QBF para evaluar la dinámica de grupos de vertebrados mayores que dominaron los ecosistemas terrestres durante el Mesozoico Temprano de Pangea.